Synthesis and Characterization of Silica from Awash Melkaasa Chemical Factory Waste - Robel Mehari Tesfaye; Fana Teklemariam; Hailemariam Aweke; Hailemariam Gebregwergis (Ethiopian Journal of Science and Sustainable Development, 2022)
Silica is a common name for the chemical compound silicon dioxide. It can be found naturally in abundant amount as sand and is a raw material for many useful chemicals like silicone and silicates. It can be also found as a by-product from several chemical factories. Awash melkassa is one of the factories that releases this silica as a waste product. In this work, this waste, that has a silica content of more than 65%, was used as a raw material for synthesis of purified silica. Here the silica was prepared by two distinct routes: basic and acidic routes. In basic route, the chemical factory waste have been leached with caustic soda to prepare sodium silicate followed by reducing the silicate with an organic acid to prepare purified silica then finally size reduction by ball milling. In the second method, inorganic acids such as sulfuric acid and hydrochloric acid have been used to remove the impurities from the chemical factory waste and ball milling the purified silica to obtain the micro particles. Characterization of the final products was done by SEM and XRD. Finally the best process for silica synthesis have been decided based on which process yields the higher silica content product which is the acidic routine.